Vapor sublimation and deposition to build porous particles and composites - Hsing-Ying Tung (Nature Portfolio, 2018)
Fabrication of porous nanoparticles is often hampered by low efficiency production methods, challenging isolation of the material and poor control over the fabrication process. Here the authors demonstrate a facile ice-template vapor-phase synthesis which allows for production of porous poly-para-xylylene particles on a large scale.